Toward a better understanding of the native-nonnative status of mytilus mussels in the Southwestern Atlantic: Comparing pre-european middens and modern populations - Savoya, Veronica (2015)
The aim of this study is to determine the degree of similarity of the Mytilus mussels currently found along the Patagonian coast of Argentina to those found in pre-European colonization middens, in order to approach an understanding of whether the former are native or not. An elliptic Fourier analysis between pre-European archaeological (native) and modern mussels (cryptogenic) was performed, and the resulting data were analyzed with multivariate approaches (principal component analysis, discriminant function analysis, and cluster analysis). Our results showed that when all samples belonging to the Patagonian coast were included on a single analysis, modern and archaeological mussels were clustered in two major groups, matching the macroregional marine biogeographic scheme. In addition, morphometric differences were detected when modern and archaeological mussels from similar latitudes were compared. We discuss these results in light of the natural and anthropogenic changes that occurred along the Argentinean coast together with the environmental changes occurring between the biogeographic provinces along the SW Atlantic coast.